Atherosclerotic Cardiovascular Disease in Rheumatoid Arthritis: Impact of Inflammation and Antirheumatic Treatment. Issue 1 (2021) - Kerola, Anne Mirjam; Rollefstad, Silvia; Semb, Anne Grete
No abstract available